Disconnectivity synced with identity cultivation: adolescent narratives of digital disconnection. Issue 6 (29th October 2022) - Agai, Mehri S
Abstract: This article elucidates adolescent digital disconnection through the lens of narrative identity development to answer the research question: "How do adolescent disconnection experiences play into ongoing identity development processes?" The study draws from qualitative interviews with 17 Norwegian adolescents. The findings indicate that adolescents are ambivalent about their relationships with social networking sites, producing ripple effects on their motivation and disconnection practices. The findings are explained through the cultivation of narrative identity. Thus, this article proposes that adolescent digital disconnection is aligned with identity formation, reflected in narrative themes and corresponding features. By detailing how ongoing identity construction processes underpin the need and ability to disconnect, this article contributes a developmental perspective to the digital disconnection literature. Lay Summary: Adolescents only know a connected world, but they admit that they disconnect from the disadvantages of constant connectivity. This study offers an inside perspective regarding the what, why, and how of digital disconnection. The findings illustrate that some adolescents "log off" spontaneously to recover from the emotional distress triggered by social media, while others endeavor to reduce their screen time in favor of personal growth. These differences seem to sync with the question, "Who am I really?" Adolescents with a sense of identity can better withstand pressure from peers to stay online, choosing disconnection or connection independently rather than because of their peers.